Merging the Psychophysical Function With Response Times for Auditory Detection of One vs. Two Tones - Lentz, Jennifer J.; Townsend, James T. (Frontiers in Psychology, 2022)
The purpose of this study is to take preliminary steps to unify psychoacoustic techniques with reaction-time methodologies to address the perceptual mechanisms responsible for the detection of one versus multiple sounds. We measured auditory redundancy gains for auditory detection of pure tones widely spaced in frequency using the tools of Systems Factorial Technology (Townsend and Nozawa, 1995) to identify the system architecture and workload capacity in two different scenarios (SOFT and LOUD). We adopted an experimental design in which the presence or absence of a target at each of two frequencies was combined factorially with two stimulus levels. Replicating previous work, results did not allow an assessment of system architecture due to a failure to observe factor influence at the level of distribution ordering for dual-target stimuli for both SOFT and LOUD scenarios. All subjects demonstrated very modest redundancy gains for the dual-target compared to the single-target stimuli, and results were similar for both LOUD and SOFT. We propose that these results can be predicted by a mental architecture that falls into the class of integrated subadditive parallel systems, using a well-supported assumption that reaction time is driven by loudness. We demonstrate that modeled loudness of the experimental sounds (which ranged between about 0.2 and 14 sones) is highly correlated with mean reaction time (r=-0.87), and we provide a proof-of-concept model based on Steven’s Power law that predicts both a failure of distributional ordering for dual-target stimuli and very modest redundancy gains.